How to close the science-practice gap in nature conservation? Information sources used by practitioners. (July 2019) - Fabian, Yvonne; Bollmann, Kurt; Brang, Peter; Heiri, Caroline; Olschewski, Roland; Rigling, Andreas; Stofer, Silvia; Holderegger, Rolf
Abstract: Professionals working in practical conservation management and scientists often complain about an information gap between science and practice. Which kinds of information sources are important to professionals and which do they use in their every-day work? Answering these questions and knowing more about the information sources used by conservation professionals would promote effective knowledge transfer from science to practice. We conducted a survey to identify the information sources used by Swiss professionals in nature conservation, including the forest sector. Experience-based information sources (e.g. personal experience, direct exchange with colleagues and experts) are more important for professionals in nature conservation than evidence-based sources (e.g. various print products such as guidelines, specialized journals in national languages, text books targeted to professionals). They were also more often used. Articles from international scientific journals are hardly ever consulted by conservation professionals. It is thus important that scientists engage as experts and take time for direct personal contact and exchange with conservation professionals (e.g. by offering field trips). Given that professionals have little time in their daily business for searching and implementing new scientific knowledge and results, short, audience-targeted and synthetizing publications in national languages as well as specialized websites should be provided by researchers. These measures are key to reduce the gap between science and practice in nature conservation. Article impact statement: Personal engagement and personal contact between scientists and conservation professionals are necessary to reduce the science-practice gap.